The Influence of Price Perception and Service Quality on Guest Loyalty with Satisfaction as an Intervening Variable on Sunday Bali Hotels & Resorts - Supandi, Dede Andri; Nurwati, Etty; Raharjo, Pamuji Gesang (Technium Social Sciences Journal, 2026)
This study aims to analyze the influence of price perception and service quality on guest loyalty with satisfaction as an intervening variable at Sunday Hotel & Resort Bali. This study uses a quantitative, survey-based approach. The study population comprised Sunday Hotel & Resort Bali guests who stayed during the study period, namely November - December 2025, with a sample of 200 respondents selected using purposive sampling, namely guests who had stayed more than twice. Data were collected through questionnaires and analyzed using the Partial Least Squares (PLS) method through SmartPLS 3 software. The results showed that price perception and service quality had a positive and significant effect on guest satisfaction. Furthermore, satisfaction also had a positive and significant effect on guest loyalty. This finding confirms that satisfaction plays a role as an intervening variable that strengthens the influence of price perception and service quality on guest loyalty.